Food Allergy and its Homoeopathic Management (Homoeopathy for All, 2021)
Viennese paediatrician Clemens von Pirquet was the first originally presented concept of allergy in 1906, when he observed that patients who had received injections of horse serum or smallpox vaccine usually had quicker, more severe reactions to second injections.1The word allergy is originated from Greek word allos meaning “other” and ergon meaning “work”.2Numbers of food allergiesare soaring gradually in worldwide and Asian countries but it is still relatively lower in Asian countries than in urbanized Western populations.3Ample data are lacking in India to estimate the prevalence of Allergy. Food allergy is the immune system’s reaction to any harmless food materials. It is estimated that food allergies affects 6% of children and 4 % of adults.4In India, from last 40 years,increase in allergic disease from 10%to 30% has been reported.5,6These diseases include hay fever, food allergies, atopic dermatitis, allergic asthma, and anaphylaxis.7Food allergy can have negative effects on the quality of life of patients and their families. Accidental exposure may happen any time hence they have remain vigilant every time. Symptoms of allergic reaction can be visible from gastrointestinal symptoms or skin rashes to severe reactions that can be fatal to children and adults.8Conventional system of medicine use to prescribe immunosuppressant as the treatment guideline for the allergic patient. In this article, we will discuss about the allergy and its homoeopathic management.
Keywords: Viennese paediatrician; Risk factors